Atividade antimicrobiana de diferentes extratos etanólicos de Agaricus brasiliensis S. Wasser et al. em estreptococos orais - Lund, Rafael Guerra (2007)
A great variety of diseases can affect the oral cavity, such as dental caries, that is considered the most prevalent oral disease worldwide. The multifactorial and infectcontagious characteristics of dental caries have been established, associated with resident bacterial pathogens of dental biofilm. These microorganisms are responsible by the production of acids and citotoxic products, which could respectively promote the demineralization of dental structure and gingival inflammation, with posterior destruction of supporting tissues. Therefore, the use of efficient antimicrobial agents against pathogenic bacteria is an important tool in the control of oral diseases. Several natural antimicrobial agents are been investigated because of their possible pharmacological properties. The mushroom Agaricus brasiliensis S. Wasser et al. ( Royal-Sun-Agaricus ) is pointed out as a natural product with noticeable antibacterial, antifungicidal, anti-inflammatory and antineoplasic properties. In this study the potential effect of this natural product was evaluated using three ethanolic crude extracts (100%, 75% and 50% EtOH) on growth and adherence of mutans streptococci. The ethanolic extracts were obtained by maceration process. Negative controls were 100%, 75% and 50% ethanol. The antimicrobial tests used against Streptococcus mutans UA 159 and Streptococcus sobrinus 6715 were agar diffusion method, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and bacterial cell adherence to a glass surface. In agar diffusion method, only the 100% etanol extract revealed a slight inhibiton of bacterial growth. Yet, in MIC and MBC tests, the three extracts presented antimicrobial properties and MIC and MBC values ranged between 87.4 and 444.5 μg/mL. The MBC for the three ethanolic extracts was similar to MIC against S. mutans, but only 75% ethanol extract was bactericidal against S. sobrinus. Among the ethanolic extracts tested, 100% ethanol extract was the most active (MIC 87.4μg/mL). The celular adherence also was inhibited at concentrations from 100 to 400 μg/mL of 50% and 75% ethanol extracts. In conclusion, the ethanolic extracts from A. brasiliensis showed remarkable inhibitory effects on bacterial growth and the 100% ethanol extract was the most active